The importance of structural change in industry for growth - Walsh, Patrick Paul; Whelan, Ciara (Statistical and Social Inquiry Society of Ireland, 2000)
The paper documents ongoing job creation and job destruction within 3- digit Irish manufacturing sectors over the period 1973 to 1994. Within sectors of low-technology manufacturing, this was due to the gradual development of historical export product lines and gradual decline in historical domestic oriented production. In contrast, the structural change in jobs within sectors of hightechnology manufacturing resulted from the gradual accumulation of foreign capital with new export product lines and a phasing out of inefficient import substituting industry. Ireland?s industrial performance is shown to be an outcome of such path dependent structural change.
Read before the Society, 25 November 1999
Keywords: Manufacturing; Intra-Sector structural change; Trade liberalisation; 314.15